Religious Traditional Treatment of Epidemics: A Legacy From Acehnese Manuscripts - Fakhriati, Fakhriati; Yusuf, Choirul Fuad (Analisa: Journal of Social Science and Religion, 2020)
Traditional medication practice roots widely across region. A number of less complex traditional medicine practices also operated within small and sometimes isolated groups based largely on local experience since the very long time ago. Historical contribution of traditional medicine as one of complementary or alternative therapy is unquestionably recognized amongst the people of the world-wide. The Acehnese manuscripts written by ulamas, aligned from Muslim prior generations within a care giver environment cannot be denied its existence. One of the important subject contents is related to traditional medication applied since the very past time. This paper describes traditional medication written in the Acehnese manuscripts, of which particularly might be useful for handling the virus appeared today. With the use of philological and historical approach, uses text and contextual analysis, the paper highlights some findings, that the three Acehnese manuscripts -- Ar-Rahmah Fi at-Tibb wa Al-Hikmah, a manuscript of Teungku Nurdin, and a manuscript of Teungku Amir -- explain traditional medical treatment preventing the disease outbreak. Historically, the Acehnese used traditional medication therapy by means of consuming herbs beside staying as close as possible to religion and intensifying prayer to God. Due to its practical function as one of effective therapy and the valuable cultural legacy, the Acehnese manuscripts of traditional medication need any professional preservation, conservation, and reproduction for enriching the Nusantara’s civilization.